Профспілки як суб'єкти соціального партнерства на стороні працівників - Шамшина, І. І.; Шамшина., И. И.; Shamshina, І. (My University, 2011)
The signiﬁ cance of the trade unions as subjects of labour law is investigated, their place in social partnership is identiﬁ ed. The gaps in legal regulation of status of trade unions in the domestic labour law are distinguished and ways to overcome them are suggested. The proposals to improve labour laws, regulating of trade union epresentation in the social partnership, are developed.
Keywords: Профспілки; Суб'єкти соціального партнерства; Трудове право; Статус профспілок; Статус профсоюзов; Трудовое право; Субъекти социального партнёрства; Профсоюзы